Irreversibility line of Ba1-xKxFe2As2 (T-c=36.9 K) superconductor studied with ac-susceptibility measurements - Pissas, M.; Zeibekis, M.; Stamopoulos, D.; Wang, CL; Ma, YW (PHYSICA C-SUPERCONDUCTIVITY AND ITS APPLICATIONS, 2012)
We have studied the phase diagram of a Ba-1 xKxFe2As2 (T-c = 36.9 K) single crystal superconductor by employing ac-susceptibility measurements, both as a function of temperature for constant external magnetic field and of magnetic dc-field for constant temperature for angles Theta = (sic)(H, c-axis) = 0 degrees, 30 degrees, 45 degrees, 60 degrees, 75 degrees and 90 degrees, between the c-axis and the magnetic field. The irreversibility lines (H-irr(T, H)) are estimated from the onset of non-zero values of the amplitude of the third harmonic susceptibility. H-irr-lines for all the studied angles can be reproduced from the equation H-irr = H-0(Theta)(1 - T/T-c)(n), with n approximate to 4/3. From the angular dependence of H-0(Theta) parameter we estimated the anisotropy of the irreversibility lines. In the temperature interval [35, T-c] the anisotropy parameter was estimated gamma = H-irr(ab)/H-irr(c) = 2.2 +/- 0.1. The measurements of the real part of the fundamental (first harmonic) ac-susceptibility chi'(T) for constant temperature as a function of dc-magnetic field revealed, for high values of the ac-field amplitude, a second peak in the critical current. The second peak line is located far from H-irr-line and exists up to T-c. Although the particular sample has high critical densities, contrary to the predictions of the Bean's model, the maximum of the imaginary part of the fundamental ac-susceptibility chi '' exhibits lower values. This behavior could be explained by assuming a reversible motion of the flux lines around the pinning centers for low values of the ac-magnetic field amplitude. (C) 2012 Elsevier B. V. All rights reserved.